Deterrent Effects of Arrests and Imprisonment in the United States, 1960-1977 - Pogue, Thomas F. ([Verlag nicht ermittelbar], 1984)
Emerging from the tradition of econometric models of deterrence and crime, this study attempts to improve estimates of how crime rates are affected by the apprehension and punishment of persons charged with criminal activity. These data are contained in two files: Part 1, State Data, consists of a panel of observations from each of the 50 states and contains information on crime rates, clearance rates, length of time served, probability of imprisonment, socioeconomic factors such as unemployment rates, population levels, and income levels, and state and local expenditures for police protection. Part 2, SMSA Data, consists of a panel of 77 SMSAs and contains information on crime rates, clearance rates, length of time served, probability of imprisonment, socioeconomic factors such as employment rates, population levels, and income levels, and taxation and expenditure information.